DISTRIBUTED REAL-TIME MEASUREMENT SYSTEMUSING TIME-TRIGGERED NETWORK APPROACH - Bilski, Piotr; Winiecki, Wiesław (International Journal of Computing, 2014)
The paper presents results of the examination of the deterministic network used by the distributed virtual instrument. Software technology applied to control measurement data transfer between the real-time components was presented. Configuration of the laboratory test stand, designed to examine deterministic network is described. Results of the research are presented and conclusions, as well as future prospects iterated.